Learning management system (LMS) and it’s perception among the stakeholder’s of educational institutes: A comprehensive review - Parantap Chatterjee; Amit Kundu; Chandan Kr. Bhattacharyya (New Applied Studies in Management, Economics & Accounting, 2022)
Learning management system (LMS) used for delivering education has become one of the most important innovative tools. It is widely used and implemented by educational institutes and universities all over the world. This paper reports on a literature review focusing on behavioural intentions of the stakeholders to adopt learning Management Systems in a multinational context. The authors examined 35 publications on the subject from 2018 to 2021, making critical analysis of theories adopted in the study, the research approach, adoption factors, barriers, constructs used and research context. The primary focus is to shed light on these contradictive objectives unfolding in this context and identify research areas that need more attention in future LMS implementation research in the educational institutes.